Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am stuck though on the way to prove this statement of fibonacci numbers by induction :

my steps:
definition: $F_{0}:=0, F_{1}:=1 $ and $F_{n}:=F_{n-1}+F_{n-2}$

The Hypothesis is: $\sum_{i=0}^{n} F_{i}=F_{n+2}-1$ for all $n > 1$

Base case: $n=2$
$\sum_{i=0}^{2} F_{i}=F_{0}+F_{1}+F_{2}=0+1+F_{1}+F_{0}=0+1+1+0=2$ which is equal to $F_{2+2}-1=F_{4}-1=F_{3}+F_{2}-1=F_{2}+F_{1}+F_{2}-1=1+1+1-1=2$ OK!

inductive step:
to prove: $\sum_{i=0}^{n+1} F_{i}=F_{n+3}-1$ for all $n > 1$
$\sum_{i=0}^{n+1} F_{i}=\sum_{i=0}^{n} F_{i}+F_{n+1}=F_{n+2}-1+F_{n+1}{n+3}-1$

i need help to $$ please! thanks a lot

share|cite|improve this question
up vote 5 down vote accepted

Use $F_{n+1}+F_{n+2}=F_{n+3}$, to get:

$$\sum_{i=0}^{n+1} F_{i}=\sum_{i=0}^{n} F_{i}+F_{n+1}=F_{n+2}-1+F_{n+1}=F_{n+1}+F_{n+2}-1=F_{n+3}-1$$

share|cite|improve this answer
why $(n+2)+(n+1) = n+3 $ in fibobacci ? – doniyor Nov 24 '12 at 8:52
So what? Stil $F_{n+3}=F_{n+2}+F_{n+1}$ holds. – Amr Nov 24 '12 at 8:54
$F_{n + k + 2} = F_{n + k + 1 } + F_{n + k}$ holds true always in the Fibonacci Sequence, as long as $n$ and $k$ are whole numbers. You could even remove the $k$ and get the correct definition. The $k$ was pushed in for better understanding. You could put infinite $k$'s in there—i.e., $k_1 , k_2\ldots$. – Parth Kohli Nov 24 '12 at 9:55

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.